MEMBANGUN KESADARAN LINGKUNGAN DALAM PENGUATAN KURIKULUM PERGURUAN TINGGI ISLAM DI INDONESIA - Musyafa, Wildayah; Pratama, Riki Adi; Amriyah, Chairul; Junaidah; Mustofa, Ikhsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Human activities such as uncontrolled industrialization, deforestation, and the exploitation of natural resources have caused severe environmental degradation, and this global ecological crisis also involves Indonesia. The presence of educational methods that can foster ecological ethics and responsibility is necessary due to the low awareness of environmental conservation. In such circumstances, Islamic education holds a strategic role because it integrates spiritual, moral, and social principles related to environmental preservation. The purpose of this study is to investigate the efforts made by Islamic higher education institutions to enhance their curricula by incorporating environmental awareness to support sustainable development. This library research employs a descriptive qualitative approach and content analysis of national and international scholarly literature (2020–2025). The results show that Islamic values such as khilafah (stewardship), mizan (balance), ‘adl (justice), and amanah (trustworthiness) serve as essential foundations for developing environmental education in Islamic universities. These values can be implemented through cross-disciplinary integration, interdisciplinary approaches, action-based ecological activities, and the use of digital media for green literacy. However, there are several challenges in strengthening these educational programs. Lecturers have limited understanding of ecopedagogy, there is a lack of policy and budgetary support, and students demonstrate low environmental awareness. According to this study, Islamic education has the potential to become a transformational tool for producing a generation of Muslims who are faithful, intelligent, and environmentally conscious. This aligns with Islamic values and the Sustainable Development Goals (SDGs).